Sustainable efficient adsorbent: Alkali-acid modified magnetic biochar derived from sewage sludge for aqueous organic contaminant removal - Tang, Lin; Yu, Jiangfang; Pang, Ya; Zeng, Guangming; Deng, Yaocheng; Wang, Jiajia; Ren, Xiaoya; Ye, Shujing; Peng, Bo; Feng, Haopeng (Chemical engineering journal (Lausanne, Switzerland : 1996), 2018)
[Display omitted] •Alkali-acid modified MS-biochar was superior to single alkali/acid modified ones in adsorption performance.•SNMS-800 owing obviously increased porosity showed enhanced TC adsorption reaching to 286.913 mg/g.•Magnetic sludge biochar’s pore size was closely related to its TC adsorption strength.•Pyrolysis temperatures showed great influence on MS-biochars’ property.•SNMS-800 showed stable TC adsorption in natural water samples along with good reusability. Municipal sewage sludge (MS)-derived biochar shows low-cost superiority as a potential adsorbent in organic contaminants removal, but limited by its poor adsorption capacity and heavy metal leaking risk. Herein, a novel and effective alkali-acid combined method was proposed for its modification and applied to tetracycline adsorption. The associative facilitation between the alkali and acid modifications was explored, and the influences of pyrolysis temperatures on MS-biochar’s properties were investigated. The successfully preserved γ-Fe2O3 vested SNMS-800 with magnetism. It turned out that SNMS-800 exhibited optimum performance for tetracycline removal with adsorption capacity up to 286.913 mg/g, where all goodness-of-fit indexes of isothermal models were measured by MPSD model. The strong adsorption mechanisms were dominated by two considerable interactions, including strong π-π stacking interaction and pore-filling effect due to the significantly enhanced porosity which was proved by density functional theory model calculations. It manifested that appropriate multiple relation (1.7–6 times) between adsorbent’s pore size and adsorbate size closely related to the adsorption strength. The remarkably improved and stable adsorption capacity, extremely low-cost, easy magnetic preparation, and good reusability in natural water samples entrusted SNMS-800 with good potential for actual aqueous contaminant removal on a large scale. Meanwhile, it provides a clue for materials modification starting with its specific components, and supplies a cost-effective way for municipal sewage sludge’s resource disposal.